Autosoliton in Ablowitz-Ladik chain with linear damping and nonlinear amplification - Abdullaev, Fatkhulla Kh. (Elsevier, 2002)
The existence of discrete autosolitons in a nonlinear lattice is studied. The Ablowitz–Ladik (AL) model with linear damping, nonlinear cubic amplification and quintic damping and complex second difference representing the discrete analog of the filter is investigated. The parameters of the autosoliton are calculated using the perturbation theory for the AL model. Analytical predictions are confirmed by numerical simulations of the AL model with nonconservative perturbations.